Ternary glycerol-based deep eutectic solvents: physicochemical properties and enzymatic activity - Rashid, Shahidah Nusailah; Hayyan, Adeeb; Hayyan, Maan; Hashim, Mohd Ali; Elgharbawy, Amal Ahmad; Sani, Fazrizatul Shakilla; Basirun, Wan Jefrey; Lee, Vannajan Sanghiran; Alias, Yatimah; Mohammed, Alaa Kareem; Mirghani, Mohamed Elwathig Saeed; Zulkifli, M.Y.; et al. (ELSEVIER (IChemE publication), 2021)
The present study investigates deep eutectic solvents (DESs) as potential media for enzymatic hydrolysis. A series of ternary ammonium and phosphonium-based DESs were prepared at different molar ratios by mixing with aqueous glycerol (85%). The physicochemical properties including surface tension, conductivity, density, and viscosity were measured at a temperature range of 298.15 K – 363.15 K. The eutectic points were highly influenced by the variation of temperature. The eutectic point of the choline chloride: glycerol: water (ratio of 1: 2.55: 2.28) and methyl triphenylphosphonium bromide:glycerol: water (ratio of 1: 4.25:3.75) is 213.4 K and 255.8 K, respectively. The stability of the lipase enzyme isolated from the porcine pancreas (PPL) and Rhizopus niveus (RNL) toward hydrolysis in ternary DESs medium was investigated. The PPL showed higher activity compared to the RNL in DESs. Molecular docking simulation of the selected DES with the substrate (p-nitrophenyl palmitate) towardPPL was also reported. It is worth noting that ternary DES systems would be viable lipaseactivators in hydrolysis reactions.